COMPOSITION OF COSTS INCLUDED IN THE PRICE OF THE PRODUCT AND THEIR DOCUMENTATION - Rakhmatullaev Mirjalol Xatam ugli (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This article describes the composition of costs included in the product cost and their documentation. Also, the structure of expenses and the problematic aspects arising in the process of their documentation are covered, and suggestions are made on them.